2017
DOI: 10.1002/jor.23755
|View full text |Cite
|
Sign up to set email alerts
|

Current review—The rise of bacteriophage as a unique therapeutic platform in treating peri‐prosthetic joint infections

Abstract: Peri-prosthetic joint infection (PJI) is one of the most serious and dreaded complications after total joint replacement (TJR). Due to an aging population and the constant rise in demand for TJR, the incidence of PJI is also increasing. Successful treatment of PJI is challenging and is associated with high failure rates. One of the main causes for treatment failure is bacterial biofilm formation on implant surfaces and the adherence of biofilm bacteria on tissue and bone next to the implant. Biofilms are prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 62 publications
1
61
0
1
Order By: Relevance
“…There are several reasons explaining the increased antibiotic resistance of biofilms compared with free bacteria: i) The extracellular matrix secreted by bacteria in the biofilm can form a physiological and metabolic barrier (17), which can prevent or greatly reduce the entry of antibiotics into cells (18,19). ii) The microenvironment in the biofilm is complex and there may be some regional differences in oxygen concentration, osmotic pressure, and pH, resulting in different susceptibility to antibiotics and other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons explaining the increased antibiotic resistance of biofilms compared with free bacteria: i) The extracellular matrix secreted by bacteria in the biofilm can form a physiological and metabolic barrier (17), which can prevent or greatly reduce the entry of antibiotics into cells (18,19). ii) The microenvironment in the biofilm is complex and there may be some regional differences in oxygen concentration, osmotic pressure, and pH, resulting in different susceptibility to antibiotics and other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…[86][87][88][89] Kaur et al investigated the use of bacteriophages for prophylactic therapy against MRSA in a PJI in vivo model, which found that coating the implant with both bacteriophages and antibiotics resulted in the best results, including a decrease in initial bacterial adherence and less bacterial burden in the adjoining tissue. 90 Bacteriophages can also inhibit conjugation to disrupt transfer of antibiotic resistance genes 91 to increase the likelihood of bacterial susceptibility to antibiotics. The benefits of utilizing bacteriophages in humans include lack of adverse reactions, limited crossresistance with antibiotics, and good ability to penetrate bacteria 91,92 suggesting that they may be useful independently and in combination with other antibiotic therapies.…”
Section: Bacteriophage Therapymentioning
confidence: 99%
“…90 Bacteriophages can also inhibit conjugation to disrupt transfer of antibiotic resistance genes 91 to increase the likelihood of bacterial susceptibility to antibiotics. The benefits of utilizing bacteriophages in humans include lack of adverse reactions, limited crossresistance with antibiotics, and good ability to penetrate bacteria 91,92 suggesting that they may be useful independently and in combination with other antibiotic therapies. However, there are challenges associated with bacteriophages, including species specificity that requires identification of the targeted biofilm organism; similarly, the polymicrobial nature of biofilms may require multiple bacteriophage strains.…”
Section: Bacteriophage Therapymentioning
confidence: 99%
“…Bacteriophages (phage) are naturally occurring viruses that target bacterial cells with high specificity while causing minimal damage to host cells making them promising preclinical agents for treatment of PJI 128 . Phages are able to adhere to the bacterial cell surface, insert its genomic material into the bacterial cell, replicate within the host cell, and lyse the bacterial cell wall resulting in cell death 128 . Importantly, decreased cellular metabolic activity such as seen in small colony variants and biofilm can effectively be targeted and killed by phages in contrast to systemic antimicrobial agents 129 .…”
Section: New Advancements In the Treatment Of Musculoskeletal Infectionmentioning
confidence: 99%